Bendera Bajak Laut di Negara Bajakan: Semiotika Perlawanan terhadap Nasionalisme Palsu - Mohammad Fikri; Fajar Ainol Yakin; Muhammad Muslim (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The phenomenon of the use of the Jolly Roger symbol, a pirate flag, in the anime One Piece by Indonesians during Independence Day in August 2025 gave rise to an interesting symbolic battle between representations of the people and the state. In this context, this article explores how popular cultural symbols can be used as a tool of visual resistance against state nationalism that is considered to be losing legitimacy, especially in the increasingly connected digital era. The Jolly Roger symbol, known as the pirate flag, is not only seen as a symbol of freedom in pop culture, but also as an expression of rejection of nationalist narratives that are considered "fake" or not representing the interests of the people. Using Roland Barthes's semiotic approach (denotation, connotation, myth) and Gramsci's and Stuart Hall's theories of cultural hegemony, this article analyzes the layered meanings of the Jolly Roger symbol in the Indonesian socio-political context. In this semiotic analysis, the symbol is understood not only as an image representing freedom or rebellion, but also as a tool to express dissatisfaction with narratives of independence and citizenship dominated by the state. Data obtained from social media posts (X/Twitter, TikTok, Instagram), memes, captions, and official statements were semiotically analyzed to see how this symbol is used to challenge the state's sole claim to the meaning of nationalism. The results show that this pirate symbol functions beyond aesthetic resistance; it also functions ideologically by creating space for alternative articulations of identity and nationhood. In a digital context, this symbol voices criticism of official narratives of independence and citizenship, opens up a crisis in existing hegemonic narratives, and creates a space for people to freely express their views and identities.